Pension reform in Southeastern Europe : linking to labor and financial market reform - Holzmann, Robert; MacKellar, Landis; Repanšek, Jana (Directions in development (Washington, D.C.). Finance., 2009)
Around the world, pension reform remains at the center of public debate. Its social, fiscal, and macroeconomic implications confront policy makers, practitioners, and academia with challenging questions. Pension systems in aging societies--in need of reform and further stressed by the pressures of globalization--require parallel reforms of the labor market and effective lifelong learning, not only to promote working longer, but to ensure that people can actually do so. At the same time, the working population should be motivated to contribute to pension schemes and prepare for old age. Diversify.